Multiplex real-time PCR detection of respiratory viruses in lower respiratory tract infections in children - Zetti Zainol Rashid,; Lee, Pei Chuan; Umi Kalsom Ali,; Muttaqillah Najihan Abdul Samat,; Tang, Swee Fong (Penerbit Universiti Kebangsaan Malaysia, 2018)
Acute respiratory infections cause significant morbidity and mortality in children. Several new respiratory viruses have been identified and co-detection of multiple viruses is commonly reported. This is part of a prospective study which aims to detect respiratory viruses by multiplex molecular method and conventional methods. Nasopharyngeal aspirate specimens were taken from hospitalised children aged less than 5 years with lower respiratory tract infections. These were tested using viral culture, immunofluorescence and Seegene Anyplex™ II RV16 real-time polymerase chain reaction. From 102 samples, 69 (67.6%) were positive by PCR, 12 (11.8%) positive by culture method and 13 (12.7%) positive by IF. A single viral pathogen was detected in 48 samples (47.1%), while 21 samples (20.6%) had co-detection of 2 to 4 viral pathogens. Respiratory syncytial virus (RSV) was most common, detected in 17 samples (16.7% of all samples), followed by adenovirus and rhinovirus in 16 (15.7%), respectively. Bocavirus was detected in 15, enterovirus in 15, influenza A in 8 and parainfluenza-4 in 4 samples, with highest occurrences in co-detection (12/15, 10/15, 5/8 and 3/4, respectively). RSV was the least likely detected in co-detection (3/17). In PCR-positive samples, 54/69 (78.3%) were patients aged up to 24 months. Molecular methods detect more viral aetiologies than conventional methods, with simultaneous detection of multiple respiratory viruses. More sensitive, specific and rapid tools to determine aetiological agents could be incorporated into diagnostic algorithms of respiratory tract infections. Interpretations, significance, and applicability in clinical practice could be further explored, particularly for patients up to 2 years old.